Small Molecule Quantification by Liquid Chromatography-Mass Spectrometry for Metabolites of Drugs and Drug Candidates - Dahal, Upendra P. (The American Society for Pharmacology and Experimental Therapeutics, 2011)
Identification and quantification of the metabolites of drugs and drug candidates are routinely performed using liquid chromatography-mass spectrometry (LC-MS). The best practice is to generate a standard curve with the metabolite versus the internal standard. However, to avoid the difficulties in metabolite synthesis, standard curves are sometimes prepared using the substrate, assuming that the signal for substrate and the metabolite will be equivalent. We have tested the errors associated with this assumption using a series of very similar compounds that undergo common metabolic reactions using both conventional flow electrospray ionization LC-MS and low-flow captive spray ionization (CSI) LC-MS. The differences in standard curves for four different types of transformations (O-demethylation, N-demethylation, aromatic hydroxylation, and benzylic hydroxylation) are presented. The results demonstrate that the signals of the substrates compared with those of the metabolites are statistically different in 18 of the 20 substrate-metabolite combinations for both methods. The ratio of the slopes of the standard curves varied up to 4-fold but was slightly less for the CSI method.